TEACHER PERCEPTIONS ABOUT TRANSFORMATIONAL LEADERSHIP OF MADRASAH HEAD WITH TEACHER PERFORMANCE AT THE MADRASAH TSANAWIYAH NEGERI KABANJAHE - Banurea, Oda Kinata; Marpaung, Syafri Fadillah (Universitas Dharmawangsa, 2019)
Teacher performance is the level of work success accomplished by a teacher with the skills and expertise in carrying out the task in accordance with the task. Teachers are instrumental in the teaching and learning process. The teacher's performance can be influenced by the leadership in the Madrasah, with the transformational leadership delivered by the head of the madrasah. The problems in this research are how the Teacher's perception of the transformational leadership of the head of the Kabanjahe Schoolis the transformation? How is the performance of Guru in kabanjahe Madrasah tsanawiyah? Is there a teacher perception relationship about the transformational leadership of the head of Madrasah with the teacher performance at the Madrasah Tsanawiyah State of Kabanjahe?. The purpose of this research is to know the teacher's perception of the transformational leadership of the head of Madrasah in the state madrasah Tsanawiyah kabanjahe, to know the performance of the teacher in the state madrasah Tsanawiyah kabanjahe, to know the relationship of teacher perception about transformational leadership of Madrasah head with teacher performance in madrasah Tsanawiyah kabanjahe. This Research is a quantitative study conducted in the Madrasah Tsanawiyah Negeri kabanjahe. The number of samples in this study was 30 teachers. Data collection is done using a poll to find out the teacher's perception of the transformational leadership of the Madrasah head and teacher performance. The analysis in this study uses correlation analysis. The results showed that the teacher's perceptual relationship to the transformational leadership of the Madrasah head was in a very strong category of 8.1% against the teacher's performance. Based on the results of the analysis is known that the teacher's perception of the transformational leadership of the Madrasah head is a positive and significant relationship to the teacher's performance, the proven pearson corelation value (0.284) is greater than the significant value of 0.128.